ІНТЕНСИФІКАЦІЯ МУЗИЧНО-ПЕДАГОГІЧНОГО ПРОЦЕСУ У ВИЩІЙ ШКОЛІ (Педагогіка вищої та середньої школи, 2022)
Two ways of the intensification of a musical and pedagogical process at higher educational institutions are examined in the article: a) improvement o f the educational system; b) change of methodological approaches. The resources of the intensification in the context o f the holistic and synergetic approach are the following: state support, the results o f latest scientific researches, the personal potential o f teachers and students, the regularities of a musical and pedagogical process.